THE PECULIARITIES OF ORAL CAVITY ENZYME FUNCTIONING IN WOMEN WITH POLYCYSTIC OVARIAN SYNDROME - J.G. Romanova; S.V. Dizik (Український стоматологічний альманах)
The aim of the study was to evaluate the functioning of the enzyme systems of oral cavity in women with polycystic ovarian syndrome.